IMPLEMENTASI PROGRAM 5S (SEIRI, SEITON, SEISO, SEIKETSU, SHITSUKE) DI SMK N 6 REJANG LEBONG - Kurniawan , Dwi; Danim, Sudarwan (Manajer Pendididikan, 2025)
IMPLEMENTATION OF THE 5S PROGRAM (SEIRI, SEITON, SEISO, SEIKETSU, SHITSUKE) AT SMKN 6 REJANG LEBONG DWI KURNIAWAN Thesis, Master's Program in Educational Administration, Faculty of Teacher Training and Education, University of Bengkulu, 2025, 99 pages. ABSTRACT This study aims to describe the implementation of the 5S program at SMKN 6 Rejang Lebong, covering planning, implementation, evaluation, and follow-up in fostering an industrial work culture within the school environment. This research employs a descriptive qualitative method using interviews, observations, and documentation techniques. Data analysis is conducted using the interactive model of Miles and Huberman. The findings indicate that the 5S program was initiated through industry collaboration, however challenges remain in ensuring consistent student adherence. Evaluation is carried out through audits and supervision, while follow-up actions include strengthening socialization efforts and improving facilities. In conclusion, the success of the 5S program depends on the commitment of all school members, clear policies, and collaboration with industry. Therefore, a more intensive strategy is required to instill an industrial work culture effectively in the school environment. Keywords: Industrial Work Culture, Implementation, 5S Program, Vocational High School